Peningkatan Kapasitas Keuangan dan Pemasaran Kelompok Tenun ”BUA MESE” Melalui Implementasi Sistem Akuntansi Berbasis Cloud dan E-Commerce - Handrianus Mentu; Natalia Lily Babulu; Adi Faisal Aksa; Fransiskus Markus Pereto Keraf; Wolfhardus Vinansius Feka (JURNAL CEMERLANG: Pengabdian pada Masyarakat, 2025)
The "Buamese" weaving group is a micro-enterprise producing traditional woven fabrics with high cultural value, but faces challenges in marketing, productivity, and financial record-keeping. This community service activity aims to improve financial management and marketing capacity through the implementation of a cloud-based accounting system and the use of e-commerce. The method used is a participatory-collaborative approach including outreach, business management and digital marketing training, technology implementation, mentoring, and evaluation. Initial results show increased digital and financial literacy, partner enthusiasm in adopting technology, and increased awareness of the importance of digital marketing to expand market access. The implementation of digital accounting applications and e-commerce strategies offers the potential to increase business management efficiency and the competitiveness of "Buamese" woven products. In conclusion, this program successfully addresses the goal of empowering partners in more modern and sustainable business management, while supporting the development of a digital technology-based creative industry and economic empowerment based on local wisdom.